How to Choose Suitable Reference Electrode and Aqueous Electrolyte to Avoid Error in Electrochemical Measurements? - Wang, Hui; Wang, Min; Wang, Jingjing (Current Chinese Science, 2023)
Objective: To reduce the experimental error, three commonly used reference electrodes (Hg/HgO, Hg/Hg2Cl2 (SCE), and Ag/AgCl) are investigated to select the appropriate electrode in different aqueous electrolytes. Methods: Besides, the correct electrochemical test method is proposed according to the stability of the reference electrode. After measuring the potential difference of reference electrode in various aqueous electrolytes, it is found that Hg/HgO electrode is suitable for alkaline electrolytes, with minimum deviation in 6 M KOH solution, SCE should be used in acidic electrolytes, with minimum deviation in H2SO4 solution less than 1 M, and both SCE and Ag/AgCl electrode can be used in neutral electrolytes. Results: Due to the liquid junction potential, the result of using the double salt bridge is more accurate than that of using the single salt bridge. Conclusion: The stability of various reference electrodes in electrolytes is discrepant. Therefore, calibration is emphasized since the potential of the reference electrode drifts and even becomes invalid after prolonged use.
Keywords: three-electrode systems